Cold Stress Response: An Overview in Chlamydomonas - Ermilova, Elena (Frontiers in Plant Science, 2020)
Low temperature (or cold) is one of the major environmental factors that limits growth and development of many plants. Various plant species have evolved complex mechanisms to adjust to temperature decrease. Low temperature (or cold) is one of the major environmental factors that limits growth and development of many plants. Various plant species have evolved sophisticated mechanisms to adjust to temperature decrease. Although mesophilic chlorophytes are widely distributed group of eukaryotic photosynthetic organisms, there is not sufficient information about key molecular processes of their cold acclimation. The best available model for studying how chlorophytes respond to and cope with variations in temperature is the unicellular green alga Chlamydomonas reinhardtii. Chlamydomonas has been widely used for decades as model system for studying the fundamental mechanisms of the plant heat stress response. At present, unraveling novel cold-regulated events in Chlamydomonas has attracted increasing research attention. This mini-review summarizes recent progress on low temperature-dependent processes in the model alga, although information for other photosynthetic organisms (cyanobacteria and land plants) has been used to strengthen generalizations or specializations of cold-induced mechanisms in plant evolution. Here, we describe recent advances in our understanding of cold stress response in Chlamydomonas, discuss areas of controversy, and highlight potential future directions in cold acclimation research.